Virtue Ethics and Legal Ethics - Dare, Tim (Victoria University of Wellington Law Review, 1998)
Tim Dare rejects the widely held view that lawyers should bring their own moral beliefs to bear in their professional lives. He rejects the current trend to favour character based accounts of ethics (virtue ethics) over rule or principle based models of ethics. Rule based approaches are necessary to professional ethics because of the important pubic role that lawyers play in implementing the agreements reached between competing interest groups in society that are enshrined in law. Moreover, he argues, for the lawyer client relationship to work it is imperative that the client is aware of the moral code that the lawyer will bring to their work. This is only possible where the moral code is public and uniform, not personal and opaque.